The Effects of Materialism and Consumer Ethics on Ecological Behavior: An Empirical Study - Bakırtaş, Hülya; Canberk Buluşa, G; Bakırtaş, İbrahim (European Journal of Sustainable Development, 2014)
World populations have increased day by day. Thus, production volume of companies have increased depend on increasing population. Besides, fashion and/or technology influence consumer’s goods or services purchasing decision. Consequently, the type and the number of product produced have increased and natural resources both more are being used and depleted. At this point has come to the fore the consumer’s environmental concern and ecological behavior and has gained importance. Studies about environmental concern in marketing began depending on living of some problems in the early 1970s. Environmental concern concept assesses in terms of both individual concern and social concern. Individual concern states to abuse of the environment of individual consumers while social concern states perceived need for social, political, and legal changes to protect the environment. There is a positive relationship between environmental concern and ecological behavior. This study was examined the relationship between materialism, consumer ethics, environmental concern and ecological consumer behavior. This study was carried out between dates of September and November 2013. To test the hypotheses of the study, regression analysis has been used. Results show that consumer ethics has positive impact on both environmental concern and ecological behaviour of consumer. Besides, materialism has negative impact on ecological behaviour. Keywords: Environmental concern, consumer ethics, materialism, ecological behavior.